Graphic narratives as pedagogical tools: Diversifying the curriculum of science in schools (Journal of Applied Learning and Teaching, 2025)
The dominant techno-scientific narratives on climate change overlook the subtext of colonial anthropocentric modes of thought that conceptualize nature as an abstract resource. The statistical record of increasing emissions and the associated solutions of sustainable management need to accommodate alternate knowledge systems that challenge colonial-extractive epistemes of human exceptionalism. This paper examines the NCERT science textbooks (IX and X) to assess the entrenchment of extractive ideologies in the curriculum and builds upon the notions of decolonizing and Indigenizing Western academia.We argue that the curriculum of science textbooks should be diversified and ecological narratives should be included by communities such as Gond artists. Graphic narratives of Gond artists can acquaint students with non-anthropocentric ways of engaging with the environment that transcend the questions of resource utilization, productivity, and yield. In doing so, the paper aims to create disciplinary intersectionality and emphasize the peripheral reference to traditional cultures in academic discussions on sustainable futures. The drawings in the graphic narrative can initiate the wider discussion of artistic practices such as environmental art, Indigenous art, and contemporary visual culture that foreground the need for epistemological changes beyond techno-scientific solutions for the climate crisis. Graphic narratives as pedagogical tools would stimulate diverse ways of thinking along with nature and provide a holistic view of the ecological crisis.